Energy Analysis of a Rotary Drum Bioreactor for Composting Tomato Plant Residues - Fahad N. Alkoaik; Ahmed M. Abdel-Ghany; Mohamed A. Rashwan; Ronnel B. Fulleros; Mansour N. Ibrahim (Energies, 2018)
Energy produced from plant residue composting has stimulated great interest in heat recovery and utilization. Composting is an exothermic process often controlled through temperature measurements. However, energy analysis of the overall composting system, especially the rotary bioreactors, is generally not well known and very limited. This study presents detailed energy analysis in a laboratory-scale, batch-operated, rotary bioreactor used for composting tomato plant residues. The bioreactor was considered as a thermodynamic system operating under unsteady state conditions. The composting process was described, the input generated and lost energy terms as well as the relative importance of each term were quantitatively evaluated, and the composting phases were clearly identified. Results showed that the compost temperature peaked at 72 h of operation reaching 66.7 °C with a heat generation rate of 9.3 W·kg−1 of organic matter. During the composting process, the accumulated heat generation was 1.9 MJ·kg−1 of organic matter; only 4% of this heat was gained by the composting material, and 96% was lost outside the bioreactor. Contributions of thermal radiation, aeration, cylindrical, and side-walls surfaces of the reactor on the total heat loss were 1%, 2%, 69%, and 28%, respectively. The information obtained is applicable in the design, management, and control of composting operations and in improvement of bioreactor effectiveness and productivity.